Are Chinese credit ratings relevant? A study of the Chinese bond market and credit rating industry - Livingston, Miles; Poon, Winnie P.H.; Zhou, Lei (Journal of Banking & Finance, 2018)
We investigate the nascent but fast-growing Chinese bond market and credit rating industry. We find Chinese bond ratings are informative and significantly correlated with bond offering yields. In addition, the Chinese bond investors distinguish ratings from different credit rating agencies (CRAs), demanding lower yields on bonds rated by global-partnered CRAs. However, the empirical results suggest that the rating scales used by Chinese CRAs are not comparable to those of international CRAs. Furthermore, Chinese CRAs have very broad rating scales and pool bonds with significantly different default risks into a single rating category, resulting in over 90% of bonds in only three rating categories.